Pharmacological modulation of edema induced by Lys-49 and Asp-49 myotoxic phospholipases A2 isolated from the venom of the snake Bothrops asper (terciopelo) - Chaves Mora, Fernando (1998)
The pharmacological modulation of edema-forming activity of Bothrops asper myotoxins II and III, Lys-49 and Asp-49 phospholipases A2, respectively, was studied plethysmographically in the mouse foot pad model. Myotoxin III had phospholipase A2 activity, whereas myotoxin II was devoid of enzymatic activity when tested on egg yolk phosphatidylcholine. Both toxins induced a dose-dependent edema of rapid onset. Chemical modification of myotoxin III with p-bromophenacyl bromide abrogated enzymatic activity and significantly reduced edemat-forming activity, although a residual effect remained. Pre-treatment of animals with diphenhydramine, dexamethasone, indomethacin and prazosin significantly reduced the effect of both myotoxins. It is concluded that (a) these myotoxins are important edema-forming components of B. asper venom, (b) enzymatic activity is not a strict requirement to exert this effect, although in the case of myotoxin III it contributes to its development, and (c) several inflammatory mediators participate in mouse foot pad edema induced by these myotoxins.